Fuzzy logic controller for an automatic car gearbox shifting - Norafiza, Mohd Hassim (2009)
Now a days, most of the car accident happened because of the malfunctioning and the bad performance of the gearbox system. To overcome this situation, a fuzzy logic controller application has been implemented to enhance the performance and the ability to contribute to a smart gearbox system. This was done by using the Microsoft Visual C# software where the Graphical User Interface (GUI) and the Fuzzy Logic algorithms were created. It used the brake, speed and the oil pedal as the input membership and the gear knob shifting as the output for the project. The Fuzzy Logic components that were implemented included the fuzzification, knowledge base, inference engines and defuzzification. As a result, the GUI gives the correct gear selection based on the fuzzy logic algorithms that has been implemented in the programming part before. As a conclusion, using this Fuzzy Logic Controller application, the system will be simpler yet easy to understand and can operates smoothly rather than other controller. Hence, this automatic gearbox system will contribute to the smart and enhance the ability and the performance ofthe automatic gearbox system.